GIANT VENOUS ANEURYSM IN A KIDNEY TRANSPLANT: CLINICAL CASE AND LITERATURE REVIEW - Mendes, Daniel (2020)
Introduction: The diagnosis of visceral venous aneurysms is typically incidental. Despite the widespread use of modern imaging methods, the identification of these lesions remains extremely rare. Renal vein aneurysms are among the rarest subgroup. Methods: We present a clinical case of a 52-year-old patient with a giant kidney transplant vein aneurysm associated with an arteriovenous fistula. Additionally, a literature review was carried out in the MEDLINE database. Results: Female patient with a history of kidney transplant from a living donor with the graft implanted in the left iliac fossa, presents to the emergency department with pain over the kidney graft and fever. Upon examination of the kidney tranplant with ultrasound, a large lesion was observed in the renal pelvis with blood flow identified on Doppler. Computerized angiotomography was performed, which revealed the presence of an arteriovenous fistula between the artery and the renal vein, with a large 5.6 cm renal vein aneurysm occupying practically the entire renal pelvis. In the first stage, embolization of renal arteriovenous fistula was performed with coils. Due to the persistence of the infection and renal graft dysfunction, she was subsequently submitted to nephrectomy of the graft. Conclusion: Renal vein aneurysms are extremely rare with only a few cases published in the literature. These aneurysms are amenable to endovascular or surgical treatment, however, given the scarcity of published data, long-term results are unknown.